Recovery of release cloud from laser shock-loaded graphite and hydrocarbon targets: in search of diamonds. (22nd December 2022) - Schuster, A K; Voigt, K; Klemmed, B; Hartley, N J; Lütgert, J; Zhang, M; Bähtz, C; Benad, A; Brabetz, C; Cowan, T; Döppner, T; Erb, D J; et al.
Abstract: This work presents first insights into the dynamics of free-surface release clouds from dynamically compressed polystyrene and pyrolytic graphite at pressures up to 200 GPa, where they transform into diamond or lonsdaleite, respectively. These ejecta clouds are released into either vacuum or various types of catcher systems, and are monitored with high-speed recordings (frame rates up to 10 MHz). Molecular dynamics simulations are used to give insights to the rate of diamond preservation throughout the free expansion and the catcher impact process, highlighting the challenges of diamond retrieval. Raman spectroscopy data show graphitic signatures on a catcher plate confirming that the shock-compressed PS is transformed. First electron microscopy analyses of solid catcher plates yield an outstanding number of different spherical-like objects in the size range between ten(s) up to hundreds of nanometres, which are one type of two potential diamond candidates identified. The origin of some objects can unambiguously be assigned, while the history of others remains speculative.